Pengaruh Pola Asuh Orang Tua Terhadap Sikap Tanggung Jawab Siswa dalam Pembelajaran Daring di kelas V SDN Gugus II Kota Bengkulu - Wahyu Widyan. A; Sri Dadi; Osa Juaraa (Universitas Bengkulu, 2022)
This study aims to analyze the effect of authoritarian, democratic, and permissive parenting on the responsible attitude of fifth graders in online learning at SDN Gugus II Bengkulu City. This type of quantitative research with comparative causal research method. The research population was all students of class V SDN Cluster II Bengkulu City, which amounted to 114 students. The sample in this study was 29 students from 114 populations. The data collection technique used a parenting style questionnaire consisting of 35 items and a student responsibility attitude questionnaire consisting of 27 items. The data analysis technique in this study used simple linear regression. The results showed that the value of tcount > ttable (3.731 > 2.056) with a significance level of = 0.05 (0.001> 0.05) and a large contribution of 34%. Furthermore, the results of the research on each aspect, namely, (1) authoritarian parenting pattern obtained t count 3.483 > 2.056 with a significance level of 0.002 < 0.05 and the amount of the contribution of 31%. (2) the results of the calculation of democratic parenting obtained tcount 4.133 > 2.056 with a significance level of 0.000 <0.05 and the amount of contribution 38.7% (3) the results of the calculation of democratic parenting obtained tcount of 1.080 < 2.056 with a contribution of 3.8 % with a significance level of 0.308 > 0.05. The conclusion in this study is that there is an influence of parenting styles on students' responsible attitudes and there is also an influence of parenting styles on aspects of authoritarian and democratic parenting on students' responsible attitudes, while permissive parenting has no effect on responsible attitudes. Keywords: Parenting Styles, Responsibility Attitude, online learning